Micropropagation of Acacia Crassicarpa A. Cunn. Ex Benth - Akeng, Griffin (2000)
Micropropagation through tissue culture technique offers an alternative to vegetative propagation to mass propagate selected trees for large-scale forest plantation. Therefore, this study aimed to develop a protocol for the micropropagation of A. crassicarpa. It involved the determination of an appropriate sterilisation technique for seeds, suitable explants to be used, appropriate plant growth regulators and medium for culture initiation and culture maintenance. Rinsing with commercial clorox (15%) for at least 15 minutes was found to be effective to reduce contamination rate to as low as 10%. Nodal stem segment and leaf obtained from 2 month-old aseptically germinated seedlings were used as explants in this study. Nodal stem segment was found to be the most appropriate explant for shoot formation when cultured on a MS medium supplemented with BAP. The highest mean number of shoots (5) and the longest mean shoot elongation (8 mm) occurred on a medium supplemented with 0.5 mg/L BAP. The longest mean shoot length (8 mm) and the highest mean number of explant obtained per culture (7) were obtained on medium without any plant growth regulator. When cultured on a medium supplemented with 2,4-D, nodal stem segment explant developed roots and callus after 14 days in culture incubation. The highest mean number of roots (8.3 =8) and the longest mean root length (12.0 =l2mm) were obtained from the medium supplemented with 10.0 and 2.0 mg/L 2,4-0 respectively while the highest intensity of callus (+++) was obtained from a medium supplemented with higher concentrations of 2,4-0 (6.0, S.O and 10.0 mg/L). Leaf explants on the other hand, failed to develop shoot when cultured on a medium supplemented with BAP where they were swollen and eventually died. However, they produced roots and callus when cultured on a medium supplemented with 2,4-0. The highest mean number of roots (20.6 =21) and the longest mean root length (10.4 =:10mm) were obtained from the medium supplemented with 10.0 and 2.0 mg/L 2,4-0 respectively while the highest intensity of callus (+++) was produced on a medium supplemented with 8.0 and 10.0 mg/L 2,4-D. The calli produced were compact, watery and white in colour.